(Invited) A Rational Design for Batteries at Nanoscale by Atomic Layer Deposition. (10th September 2015) - Liu, Chanyuan; Gillette, Eleanor; Chen, Xinyi; Pearse, Alexander J; Kozen, Alexander C; Schroeder, Marshall A; Gregorczyk, Keith; Lee, Sang Bok; Rubloff, Gary W
Abstract : A self-aligned nanostructured battery fully confined within a single nanopore presents a powerful platform to determine the rate performance and cyclability limits of nanostructured storage devices. Atomic layer deposition (ALD) has enabled us to create and evaluate such structures, comprised of nanotubular electrodes and electrolyte confined within anodic aluminum oxide (AAO) nanopores. This nanopore battery displays exceptional power-energy performance and cyclability when tested as a massively parallel device (~2billion/cm 2 ), each with ~1mm 3 volume (~1fL). (1) Cycled between 0.2V and 1.8V, this full cell has capacity retention of 95% at 5C rate and 46% at 150C, with more than 1000 charge/discharge cycles. Further increase of full cell output potential is also demonstrated. These results demonstrate the promise of ultrasmall, self-aligned/regular, densely packed nanobattery structures as a testbed to study ionics and electrodics at the nanoscale with various geometrical modifications and as a building block for high performance energy storage systems.